The planar cell polarity pathway drives pathogenesis of chronic lymphocytic leukemia by the regulation of B-lymphocyte migration - Kaucká, Markéta; Plevová, Karla; Pavlová, Sárka; Janovská, Pavlína; Mishra, Archana; Verner, Jan; Procházková, Jirina; Krejcí, Pavel; Kotasková, Jana; Ovesná, Petra; Tichy, Boris; Brychtová, Yvona; et al. (Cancer research, 2013)
The planar cell polarity (PCP) pathway is a conserved pathway that regulates cell migration and polarity in various contexts. Here we show that key PCP pathway components such as Vangl2, Celsr1, Prickle1, FZD3, FZD7, Dvl2, Dvl3, and casein kinase 1 (CK1)-ε are upregulated in B lymphocytes of patients with chronic lymphocytic leukemia (CLL). Elevated levels of PCP proteins accumulate in advanced stages of the disease. Here, we show that PCP pathway is required for the migration and transendothelial invasion of CLL cells and that patients with high expression of PCP genes, FZD3, FZD7, and PRICKLE1, have a less favorable clinical prognosis. Our findings establish that the PCP pathway acts as an important regulator of CLL cell migration and invasion. PCP proteins represent an important class of molecules regulating pathogenic interaction of CLL cells with their microenvironment.
Keywords: signální transdukce; upregulace; Membrane Proteins; Signal Transduction; Humans; Up-Regulation; Cell Polarity; lidé; zvířata; myši; chronická lymfatická leukemie; B-lymfocyty; Mice; Wnt Signaling Pathway; Leukemia, Lymphocytic, Chronic, B-Cell; signální dráha Wnt; polarita buněk; pohyb buněk; transplantace heterologní; B-Lymphocytes; Cell Movement; membránové proteiny; Animals; Transplantation, Heterologous